Helical repeat of DNA in the nucleosome core particle. (August 2000) - Negri, R.; Buttinelli, M.; Panetta, G.; De Arcangelis, V.; Di Mauro, E.; Travers, A.
Abstract : Although the crystal structure of nucleosome core particle is essentially symmetrical in the vicinity of the dyad, the linker histone binds asymmetrically in this region to select a single high-affinity site from potentially two equivalent sites. To try to resolve this apparent paradox we mapped to base-pair resolution the dyads and rotational settings of nucleosome core particles reassembled on synthetic tandemly repeating 20 bp DNA sequences. In agreement with previous observations, we observed (1) that the helical repeat on each side of the dyad cluster is 10 bp maintaining register with the sequence repeat and (2) that this register changes by 2 bp in the vicinity of the dyad. The additional 2 bp required to effect the change in the rotational settings is accommodated by an adjustment immediately adjacent to the dyad. At the dyad the hydroxyl radical cleavage is asymmetric and we suggest that the inferred structural asymmetry could direct the binding of the linker histone to a single preferred site.